2007
DOI: 10.1002/ana.21173
|View full text |Cite
|
Sign up to set email alerts
|

Moving with or without will: functional neural correlates of alien hand syndrome

Abstract: Alien hand syndrome is a rare neurological disorder in which movements are performed without conscious will. By using functional magnetic resonance imaging in a patient with alien hand syndrome after right parietal lesion, we could identify brain regions activated during involuntary or voluntary actions with the affected left hand. Alien hand movements involved a selective activation of contralateral primary motor cortex (M1), presumably released from conscious control by intentional planning systems. By contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 20 publications
6
70
1
Order By: Relevance
“…The posterior variant more commonly affects the non-dominant (left) hand [23]. It is associated with strong feelings of estrangement from the affected limb, less complex motor activity (e.g., limb levitation, ataxia, non-purposeful or nonconflicting movements), and parietal sensory deficits (visual o r s e n s o r y n e g l e c t , b o d y s c h e m a d y s f u n c t i o n , hemiasomatognosia, spatial neglect, or astereognosis).…”
Section: Posterior Variantmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior variant more commonly affects the non-dominant (left) hand [23]. It is associated with strong feelings of estrangement from the affected limb, less complex motor activity (e.g., limb levitation, ataxia, non-purposeful or nonconflicting movements), and parietal sensory deficits (visual o r s e n s o r y n e g l e c t , b o d y s c h e m a d y s f u n c t i o n , hemiasomatognosia, spatial neglect, or astereognosis).…”
Section: Posterior Variantmentioning
confidence: 99%
“…It is associated with strong feelings of estrangement from the affected limb, less complex motor activity (e.g., limb levitation, ataxia, non-purposeful or nonconflicting movements), and parietal sensory deficits (visual o r s e n s o r y n e g l e c t , b o d y s c h e m a d y s f u n c t i o n , hemiasomatognosia, spatial neglect, or astereognosis). The lesion is typically in the non-dominant (right) parietal lobe (posterior postcentral gyrus, posterior primary sensory cortex, and tertiary somatosensory cortex in the superior parietal lobule) [23]. Uncommonly, the occipital lobe and thalamus are involved [24].…”
Section: Posterior Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…One notable exception is an functional magnetic resonance imaging (fMRI) study of a patient with extensive right parietal lobe damage, who performed spontaneous (flexion-extension) movements of the left hand (fingers) without conscious will (Assal, Schwartz & Vuilleumier, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological findings have demonstrated that patients with selective lesions in PPC lose the early subjective experience of wanting to move, being aware of their movement only when it is about to be executed (7). A recent study also indicated that circumscribed lesions of the PPC can cause the occurrence of alien movements generated without conscious intention through the recruitment of the precentral executive motor regions (8).…”
mentioning
confidence: 98%